APPLICATION OF THE САSE-METHOD TO TEACHING PRACTICAL TRAINING “SYMPTOMS AND SYNDROMES OF PNEUMONIAS, PLEURISIES AND LUNG CANCER” FOR THE THIRD YEAR’S FOREIGN STUDENTS OF THE MEDICAL FACULTY - Konstantynovych, T.V.; Demchuk, H.V. (World of Medicine and Biology, 2013)
Aim of the research: assessment of efficacy of the case-method to teaching the propedeutics to internal medicine for the English-speaking foreign students. During the practical training “Symptoms and syndromes of pneumonias, pleurisies and lung cancer” 16 English-speaking medical students were proposed for study and discussion of 2 clinical cases. Collective work on the clinical cases contributed to improvement of the practical skills of the patient examination, deliberation of the received data, revealing symptoms and signs of the syndromes, making primary diagnosis with administering instrumental and laboratory investigations. The case-method increased motivation and interest of the students in the medical education.
Keywords: case-method; community-acquired pneumonia; education; practical skills